Pendidikan Literasi Ziswaf Berbasis Masjid untuk Pemberdayaan Ekonomi Jamaah Melalui Program Edukasi Keuangan Syariah - Zainur; Ali Muddin Jailani; Apriadi (Jurnal Dedikasi Pengabdian Pendidikan, 2026)
Mosques play an important role in community economic empowerment through effective management of Zakat, Infak, Sedekah, and Wakaf (ZISWAF). This community service program conducted in August 2025 with aimed to improve ZISWAF literacy and strengthen sharia financial management skills of congregants through mosque based education. The program was implemented using participatory methods including socialization activities, sharia finance training, formation of a ZISWAF management team, development of simple transparent reporting systems, and continuous mentoring. Data were collected through observation, documentation, and participant evaluation. The results showed increased understanding of ZISWAF principles, improved managerial capacity of mosque administrators, and establishment of a structured ZISWAF unit supported by digital financial reporting. In addition, productive fund distribution was initiated through microbusiness capital assistance and productive waqf programs. The discussion indicates that education based ZISWAF management can shift practices from charity oriented models toward sustainable empowerment approaches. This program strengthens the mosque’s function as a socio economic institution and encourages community participation in Islamic social finance. Overall, mosque based financial literacy education provides a economic independence welfare of Muslim communities.